Business owners’ feedback toward adoption of open data: a case study in Kuwait - Alawadhi, Nayef; Taha Alshaikhli, Imad Fakhri; Alkandari, Abdulrahman; Chab, Siba Kalaie (Hindawi, 2021)
The world intention toward open data technology has increased in the past years, and governments started to explore open data technology in the public and private sectors and tried to check its advantages and disadvantages. However, in the Arab world and especially in Kuwait, there is no solid structured attention about the technology in both sectors. As a result, we tried in this paper to determine if business owners in Kuwait have enough knowledge of the open data (OD) concept and if they have the willingness to use it for enhancing their services. The purpose of this research is to measure the acceptance of OD technology in Kuwait and to gather business owners’ opinions about the ability to adopt the OD concept. Making online and hardcopy Survey was our method for gathering different reactions and points of view about this technology. We intended to focus on the private sector and we targeted people who own a business and wish to introduce better services for their customers. Overall, the results have shown clear features about open data technology in Kuwait and the substantial need of education and awareness of the importance of this technology. The results of this study may positively and directly affect the level of motivation for other existing studies.